Thin polycrystalline silicon process development - Muniyati Pakhuruddin
The objective of this project is to fabricate thin polycrystalline silicon film with lower resistivity and higher quality of surface by converting available deposited amorphous silicon film (by Radio Frequency (RF) Plasma Enhanced Chemical Vapor Deposition) into polycrystalline silicon film by crystallization using conventional furnace annealing.